The Moderating Role of Development Financial Institutions on the Association Between Digital Technology and the Financial Performance of SMEs - Idris Adamu Adamu; Musa Musa Muhammad; Ahmad Aliyu Palladan (Journal of Economic Education and Entrepreneurship Studies, 2025)
Small and Medium-Sized Enterprises (SMEs) constitute an important segment economically in the world. However, insufficient digital transformation and ease of financing negatively affects their financial performance. This study explores the moderating role of Development Financial Institutions (DFIs) on the association between digital technology adoption and financial performance in SMEs. The study adopts a cross-sectional survey design to collect primary data from SMEs on their digital technology usage, financial performance, and access to DFI financing. The population of the study consists of existing SMEs in Zaria metropolis. A total of 237 questionnaires were administered. However, 228 questionnaires were returned and the data collected were coded accordingly. The findings of the study reveal that DFIs significantly strengthen the positive effects of digital technologies. The findings support the role of DFIs in financing digital adoption in improving financial performance.